Detection of miR-133a-5p Using a Molecular Beacon Probe for Investigating Postmortem Intervals - Eun Hye Lee; Mingyoung Jeong; Kwangmin Park; Dong Geon Lee; Eun Ju Lee; Haneul Lee; Ah Yeoung Kim; Jae Won Ahn; Hyun Jun Woo; Sunghyun Kim; Jaewon Lim; Jungho Kim (Non-Coding RNA)
Background: When a body is discovered at a crime or murder scene, it is crucial to examine the body and estimate its postmortem interval (PMI). Accurate estimation of PMI is vital for identifying suspects and providing clues to resolve the case. MicroRNAs (miRNAs or miRs) are small non-coding RNAs that remain relatively stable in the cell nucleus even after death-related changes occur. Objective: This study developed a molecular beacon probe for mmu-miR-133a-5p and assessed its use in mouse muscle tissue at temperatures of 4 °C and 21 °C to estimate the PMI. Methods: A total of 36 healthy adult male BALB/c mice were divided into 9 PMI time points (0, 2, 6, 8, and 10 days) with 3 mice per time point, and they were exposed to 4 °C and 21 °C. Next, the expression pattern of mmu-miR-133a in the skeletal muscle tissue over a 10-day PMI period was analyzed using the developed molecular beacon probe. Results: The molecular beacon (MB) probe was designed for optimal thermodynamic stability with a hairpin structure that opened in the presence of mmu-miR-133a-5p, thus separating the fluorophore from the quencher and resulting in a strong fluorescence signal at 495 nm. Fluorescence intensity increased with mmu-miR-133a-5p concentration from 1 ng/μL to 1000 ng/μL and exhibited a strong correlation (R2 = 0.9966) and a detection limit of 1 ng/μL. Subsequently, the expression level of mmu-miR-133a-5p was observed to be stable in mouse skeletal muscle tissue at both 4 °C and 21 °C. Conclusions: This user-friendly assay can complete measurements in just 30 min after RNA extraction and is suitable for point-of-care testing, and it possesses the potential to improve existing complex and time-consuming methods for PMI estimation.